Aguidance In Utilizing The Waste Utilization of The Free Nutritional Meal Program And Trash Fish In Improving The Quality of Poultry Pellet Feed In The Merak Farmers Group, Labuhanbatu District - Yudi P Prayoga; M. Yasir Arafat Pohan; Bayu Eko Broto; Muhammad Syafii; Sayyidina Umar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The availability of affordable and high-quality feed is an important factor in the sustainability of poultry farming. The Merak Farmers Group in Labuhanbatu Regency faces high commercial feed costs, while food waste generated from the Free Nutritious Meal Program and locally available trash fish have not been optimally utilized. This community service program aimed to improve farmers’ knowledge and practical skills in processing leftover rice, tofu, and tempeh from the Free Nutritious Meal Program, as well as trash fish, into raw materials for poultry pellet feed. The program applied a participatory approach through education, demonstration, hands-on practice, and production assistance. The implementation consisted of two main activities. The first activity involved sorting, drying, milling, and sieving food waste into feed meal. The second activity involved processing trash fish into fish meal, formulating the feed by adding rice bran, ground corn, and minerals, mixing the ingredients, producing pellets using a pellet machine, and drying the final product. The results showed that group members were able to carry out the processing stages and operate both the milling and pellet-making machines. The resulting pellets were relatively uniform, compact, easy to handle, and suitable for storage after drying. The utilization of locally available materials and previously underutilized resources reduced the amount of purchased feed ingredients, resulting in lower feed production costs compared with the full use of commercial feed. This program demonstrates that practice-based assistance can strengthen farmers’ capacity to produce alternative feed while supporting productive and sustainable waste management.